PENGARUH KONSERVATISME AKUNTANSI DAN INTENSITAS MODAL TERHADAP PENGHINDARAN PAJAK DENGAN DEWAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2017 - Safitri, Wetti; Fatahurrazak, Fatahurrazak (MEASUREMENT : Jurnal Program Studi Akuntansi, 2020)
This study aims to determine the effect of accounting conservatism, capital intensity, and independent board of commissioners on tax avoidance and the existence of an independent board of commissioners as a moderating variable to influence the relationship between accounting conservatism and capital intensity on tax avoidance. Tax avoidance is measured by cash effective tax rate (CETR), accounting conservatism is measured by earning / accrual measure, capital intensity is measured by the ratio of fixed asset intensity and independent board of commissioners is measured by the percentage of independent board of commissioners. The population in this study is the Manufacturing Companies sub-sector of the consumer goods industry which is listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period. The research sample was obtained using the purposive sampling method, so that a total of 84 research samples were obtained. The type of data used is secondary data with multiple linear regression analysis methods and moderated regression analysis (MRA) with the SPSS Analysis Program. The results showed that accounting conservatism, capital intensity and the independent board of commissioners influence tax avoidance, the independent board of commissioners weakens the relationship between accounting conservatism and tax avoidance and the independent board of commissioners strengthens the relationship between capital intensity and tax avoidance.